2016
DOI: 10.1371/journal.pone.0153920
|View full text |Cite
|
Sign up to set email alerts
|

Lower Methylation of the ANGPTL2 Gene in Leukocytes from Post-Acute Coronary Syndrome Patients

Abstract: DNA methylation is believed to regulate gene expression during adulthood in response to the constant changes in environment. The methylome is therefore proposed to be a biomarker of health through age. ANGPTL2 is a circulating pro-inflammatory protein that increases with age and prematurely in patients with coronary artery diseases; integrating the methylation pattern of the promoter may help differentiate age- vs. disease-related change in its expression. We believe that in a pro-inflammatory environment, ANG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…In total, 51 articles met our eligibility criteria (Supplementary Table 1) and were included in the analysis. Of the 51 selected studies, 17 included participants from Europe [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] 14 from China [23][24][25][26][27][28][29][30][31][32][33][34][35][36], six from USA [37][38][39][40][41][42], three from India [43][44][45], two from Canada [46,47], and one each from Japan [48], Malaysia [49], Iran [50], Russia [51], Brazil [52] and Mexico [53]…”
Section: Resultsmentioning
confidence: 99%
“…In total, 51 articles met our eligibility criteria (Supplementary Table 1) and were included in the analysis. Of the 51 selected studies, 17 included participants from Europe [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] 14 from China [23][24][25][26][27][28][29][30][31][32][33][34][35][36], six from USA [37][38][39][40][41][42], three from India [43][44][45], two from Canada [46,47], and one each from Japan [48], Malaysia [49], Iran [50], Russia [51], Brazil [52] and Mexico [53]…”
Section: Resultsmentioning
confidence: 99%
“…Details on the inclusion and exclusion criteria have been previously described elsewhere. 17,18 Importantly, AMI (ST elevation myocardial infarction or non-ST elevation myocardial infarction) was based on the universal definition. 19 For more detailed information on the exclusion criteria see section S1 of the Supporting Information.…”
Section: Participantsmentioning
confidence: 99%
“…ANGPTL2 expression is regulated by DNA methylation. Nguyen et al have shown that DNA hypomethylation in the promoter region of ANGPTL2 was associated with post‐ACS differently from that of age‐matched healthy controls . Nevertheless, to the best of our knowledge, no experiments have been conducted to demonstrate the correlation between the promoter methylation of the ANGPTL2 gene and the risk of CHD in a Han Chinese population.…”
Section: Introductionmentioning
confidence: 95%
“…Nguyen et al have shown that DNA hypomethylation in the promoter region of ANGPTL2 was associated with post-ACS differently from that of age-matched healthy controls. 17 Nevertheless, to the best of our knowledge, no experiments have been conducted to demonstrate the correlation between the promoter methylation of the ANGPTL2 gene and the risk of CHD in a Han Chinese population. The aim of the present study was to assess whether aberrant promoter methylation of the ANGPTL2 gene was associated with the risk of CHD in Han Chinese on the coast of China and to explore the interaction between methylation levels and clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation